Arquitetura verticalizada em madeira: projeto para um polo ambiental em Recife-PE - Melo, Lucas Figueiredo de (2021)
This work of dissertation conclusion of a professional master also consists in a technical report and architectonic project, as a preliminary study of a public institutional building intended to become the headquarters of environmental public agencies of the estate of Pernambuco as well as the city of Recife, emphasizing wooden vertical structural systems, based on a tectonic approach, added to legal and climate conditionings of the city of Recife. In order to support the project development, in the first instance, has been conducted a theoretical-conceptual analysis of the main subject and specific subthemes related to the core of the proposal, based on bibliography researches and study analysis of alike buildings. In this described procedural design, a description of the intervention area has been performed and its legal aspects have been analysed. Subsequently, an architectonical program has been created so as to define dilemmas and design guidelines. Based on these terms and supported by academic disciplines, the design guidelines was gradually developed and mapped through a variety of registers, since its initial steps of conditioning studies, conception, and development of the architectural parti to the unfolding of the final design. Considering some specific goals, it has been intended to optimize project solutions to enhance wooden structural performances on climate and environmental conditionings of intervention areas in addition to developing a proposal that reflects the institutional principles based on sustainability and permeability concepts. The results found, consist in a preliminary study of the architecture and description of the process, reaching guidelines and design solutions, as well as reflections of challenges throughout verticalized wooden designs, following the context of Brazilian civil construction. At the end, was concluded that the performance of a wooden building is closely related to the whole process and to project decisions which in this design, considered the protection of the constructive elements according to direct exposure of adverse weather conditions, overall, related to common structural elements structurally requested.